E-037 Initial Multi-Centre Experience with the Penumbra PC 400 Detachable Coil in aneurysms 10 mm or greater. (14th July 2013) - Chaudry, I; Frei, D; Baxter, B; Patel, A; Huddle, D; Loy, D; Moyle, H; Polykarpou, M; Patel, A; Turner, R; Turk, A
Abstract : Background: Aneurysm coil technology has changed considerably since the introduction of the GDC coil. We evaluated our initial clinical experience with a novel 0.020 Penumbra PC 400 coil to determine device safety and acute performance. Materials and Methods: Between 2/2011 and 9/2012, 143 aneurysms were coiled with Penumbra PC 400 coils at four high volume centres. Of these, 40 aneurysms had a maximum diameter of 10 mm or greater. Average aneurysm size in this cohort was 13 mm with 20% of aneurysms being ophthalmic in location, 22% other ICA (cavernous, superior hypophyseal or dorsal wall), 17% in ACOM region, 12.5% PCOM, 15% Basilar, 7.5% vertebral and 5% in the MCA. 18% of the cases were treated with balloon assisted coiling, 33% were stent assisted coiling, and 3% utilised both balloons and stents. 30% of the cases achieved an initial Raymond Scale of 1, 25% achieved a Raymond scale of 2, and 45% were Raymond Scale of 3. Half (20) of this patient cohort have angiographic follow up at the time of this abstract. Based on the same/better/worse scale there is a strong trend towards improved angiographic outcomes at 6 months and one year. Eleven had improved, 6 remained unchanged and 2 worsened, none have required retreatment. We experienced a 5% clinically significant procedural complication rate, which include an aneurysm perforation in a 21 mm right dorsal wall ICA aneurysm that presented as a grade 4 Hunt and Hess SAH who expired and a temporal lobe infarct secondary to distal coil migration during treatment of an 18 mm paraophthalmic aneurysm in a grade 4 Hunt and Hess SAH patient that expired from SAH sequellae. We continue to use the coils and accrue follow up and will update results at time of the meeting. Discussion: The new Penumbra PC 400 coils are a unique 0.020 coil that appears to be safe and effective in treating large aneurysms. Disclosures: I. Chaudry: 2; C; Penumbra, Microvention, Covidien. D. Frei: None. B. Baxter: None. A. Patel: None. D. Huddle: None. D. Loy: None. H. Moyle: None. M. Polykarpou: None. A. Patel: None. R. Turner: None. A. Turk: 1; C; Penumbra.